Strain gradient development in 3-dimensional extracellular matrix scaffolds during in vitro mechanical stimulation. Issue 1 (2nd January 2017) - Seifer, Benjamin J.; Wagner, Christopher T.
Abstract: This study analyzed strain variations in 3D ECM scaffolds using a membrane-adherent model (MM) and a direct elongation model (DM). Computational models were solved for target strains from 1 to 10% at varied scaffold thicknesses and intra-scaffold slices. DM strain profiles were uniform within the scaffold and independent of thickness. However, a wide range of strains developed with substantial volume experiencing significantly off-target strain. MM strain profiles varied throughout the scaffold, exhibiting significantly reduced average strain with increasing thickness. These findings are important for tissue engineering studies since biological responses are commonly attributed to a single strain level that only partially describes the mechanical condition, making it difficult to develop precise causal relationships. Spatial strain variations and reduced average strain may warrant targeted sampling for cell response and should be taken into consideration by investigators using large-volume 3D scaffolds when engineering mechanically sensitive tissues.